Asymmetric communication: How do we communicate with our pets and about them? - Kamandulytė-Merfeldienė, Laura; Dabašinskienė, Ineta (Taikomoji kalbotyra, 2023)
The emotional bond between pets and their owners is intimate in many cultures, where pets are often regarded as family members or even children. Communication with pet animals is frequently likened to infant/child-centered speech situations (Mattiello et al. 2021: 150). Pet owners commonly employ specific language forms that convey sympathy, empathy, or playfulness. This study aimed to explore the characteristics of pet-directed speech in Lithuanian, utilizing a questionnaire survey conducted through the Google Forms platform.Survey data reveal that women, predominant in this study, often perceive pets, particularly dogs and cats, as family members, bestowing upon them the status of children. This is evidenced by the frequent use of diminutives and onomatopoeia. The profusion of adjectives employed to depict pets supports the assertion that such communication is influenced by anthropomorphism, attributing human-like characteristics to pets. The regular use of diminutives when addressing pets or describing their belongings, such as food and toys, indicates that diminutives serve a pragmatic function. They make the speech act more playful, enabling owners to accomplish their goals in a less formal, friendlier manner, even when discussing less pleasant topics.
Keywords: asymmetric communication; pet directed speech; diminutive; onomatopoeia; adjective